Qualitative exploration of the impact of COVID-19 on the food environment of urban informal settlements of Dhaka, Bangladesh - Sabrina Rasheed; George Smith; Daniel D Reidpath; Shehrin Shaila Mahmood; Fatema Khatun; A M Rumayan Hasan; Mohammad Abdus Selim (BMJ Open)
Objective Our study explored the impact of the COVID-19 pandemic on the food environment from the perspective of the urban poor and food vendors.Design This was a qualitative study conducted during September 2020 and February 2021.Setting The study was carried out in two purposively selected informal settlements of Dhaka City, Bangladesh.Participants We conducted 21 in-depth interviews with residents of informal settlements and 10 key informant interviews with food vendors and food aid workers.Result The availability of staple foods was not disrupted during the pandemic but some perishables foods became more expensive due to supply chain disruptions and increased transportation costs. Limited market hours affected market access and mobility restrictions adversely affected local vendors. Cart vendors selling perishables incurred business losses they could ill afford. Demand for food reduced as employment disruption lead to reduced purchasing power and, therefore, reduction of quantity, quality and desirability of foods purchased. Respondents reported skipping meals and going hungry. The aid received was considered inadequate to meet needs.Conclusion The food environment of the urban poor was disrupted from both supply and demand sides and the organisational response (both government and non-government) was severely inadequate. The social safety net needs to be extended and redesigned to ensure food security and health for the urban working poor in the future.